Enhancement of AhR-mediated activity of selected pollutants and their mixtures after interaction with dissolved organic matter - Bittner, Michal; Macikova, Petra; Giesy, John P; Hilscherova, Klara (Environment international, 2011)
Dissolved organic matter (DOM) in freshwaters is present at concentrations ranging from 0.5 to 50 mg L⁻¹, and consists of various organic compounds, including humic substances (HS). HS exert a variety of direct and indirect biological effects, including interaction with the aryl hydrocarbon receptor (AhR). AhR is a cytosolic receptor that binds various hydrophobic organic compounds (HOCs) and mediates some of their toxic effects. In vitro effects of binary mixtures of various DOM (mainly HS) with various HOCs on AhR-mediated responses were studied by use of H4IIE-luc cells. Six out of 12 DOM activated the AhR even at environmentally relevant concentrations (17 mg L⁻¹). In simultaneous exposures of H4IIE-luc cells to DOM (17 mg L⁻¹) and each of the model compounds, 2,3,7,8-TCDD, PCB126, PCB169, benzo[a]pyrene, benzo[a]anthracene, dibenz[a,h]anthracene, fluoranthene, a mixture of persistent organic pollutants (POPs), a mixture of polycyclic aromatic hydrocarbons (PAHs), and a mixture of all HOCs, either significant additive or facilitative effects were observed when compared to activities of single HOCs. No significant decrease of effects due to possible sorption of HOCs to DOM was observed, even in subsequent experiments when HOCs+DOM mixtures were preincubated for six days before exposure to H4IIE-luc. Thus, DOM does not seem to protect organisms against AhR-mediated toxic effects of HOCs (as usually predicted due to sorption of HOCs on DOM), but it can actually enhance their potency for AhR-mediated effects in some situations.
Keywords: polycyklické aromatické uhlovodíky; polychlorované dibenzodioxiny; fluoreny; receptory aromatických uhlovodíků; Polychlorinated Dibenzodioxins; Anthracenes; huminové látky; Hydrophobic and Hydrophilic Interactions; krysa rodu Rattus; Polycyclic Aromatic Hydrocarbons; zvířata; látky znečišťující životní prostředí; anthraceny; sladká voda; Environmental Pollutants; Fresh Water; Humic Substances; Receptors, Aryl Hydrocarbon; organické látky; Benzo(a)pyrene; Fluorenes; Organic Chemicals; nádorové buněčné linie; Rats; Animals; Cell Line, Tumor; benzopyren; hydrofobní a hydrofilní interakce